KEBIJAKAN PENGELOLAAN TELUK BERBASIS DAERAH ALIRAN SUNGAI (STUDI KASUS TELUK KENDARI) - apriyanto, heri (Jurnal Sains dan Teknologi Indonesia, 2007)
Bay has an important role for regional development.Bay can be functioned as an “economic installation” such as harbor, marine industry, fishery, and tourism area but in other side it has a lot of problems. Generally, bay is an outlet of river flow areawith the result that sedimentation and pollution are always happened in this area. Based on this situation, bay management should consider the influence of the upland area. Handling bay will be more effectively if it handles together with river flow area comprehensively.That why it is important to use the approach of bay management based on river flow area like Kendari Bay in Kendari City, the Province of Sulawesi Tenggara. Kendari Bay is part of the system of Wanggu River Flow Area. This river flow area covers the District of Konawe Selatan and Kendari City. Kendari Bay has been facing serious problem of water shallow caused by sedimentation.